Tafsir Sastra Kontemporer Oleh Amin Al-Khuli Dan Aisyah Abdurrahman Bint Al-Syathi’ - Aisy Najiha Khurin’in (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2023)
This article discusses the patterns in contemporary literary methods offered by Amin al-Khuli to the world of interpretation. The author finds that Amin al-Khuli gives the tendency of mufassir in interpreting the Qur'an, so that interpretation is more oriented towards hudalinnas and uses the concept of the Qur'an as the book of Salih li kulli al-zaman wa al-makan. The literary approach brought by Amin al-Khuli was then interpreted by his student Aisyah Abdurrahman Bint al-Syathi' who was none other than his wife. Bint al-Syathi' then applied this method in his commentary which includes the first fourteen Makiyyah chapters entitled al-Tafsir al-Bayan li al-Qur'an al-Karim.